Ten year recurrence time between two major earthquakes affecting the same fault segment. Issue 7 (3rd April 2014) - Vallée, Martin; Satriano, Claudio
Abstract : Earthquake ruptures stop when they encounter barriers impeding further propagation. These barriers can theoretically originate from changes of geometry or nature of the seismic faults or from a strong lowering of the tectonic stresses, typically due to the occurrence of a recent major earthquake. We show here that this latter mechanism can be ineffective at stopping rupture expansion: the 17 November 2013 magnitude 7.8 Scotia Sea earthquake has propagated into a 100 km long zone already ruptured 10 years ago by a magnitude 7.6 earthquake. Given the plate velocities between Scotia and Antarctic plates (8–9 mm/yr), simple recurrence models would have predicted that the segment affected by the 2003 earthquake could not be reruptured by a major earthquake during several hundreds of years. This earthquake pair indicates that the variations of the tectonic stress during the seismic history of the fault are small compared to the stresses dynamically generated by a large earthquake. Key Points: Two major earthquakes occurred within 10 years on the same fault segment Recurrence time of major earthquakes can be very irregular Stress drop of a recent earthquake can be overcome by dynamic seismic stresses